Evaluation of the expanded glass as a light concrete aggregate - Gulengul, Sema; Kar, Filiz (Springer Int Publ Ag, 2022)
In this study, lightweight concretes were produced using the expanded glass and natural sand in different proportions (expanded glass ratio: 5%, 10%, 15%, 20%). The same mortar mixtures were re-prepared by adding the fluidizer. Lightweight aggregate concretes produced in the volume of 100 mm x 100 mm x 100 mm were investigated in terms of compressive strengths, elasticity modulus, thermal conductivity, water absorption rates, and unit weights. The density of concrete samples containing expanded glass was 1.5-2.2 g/cm(3), water absorption rates were 4-16.69%, heat conduction coefficient was 1-0.063 W/m K, the 28-day compressive strengths varied between 18.3 and 68.8 MPa. As the expanded glass rate increased, the density of concrete samples, the water absorption rate, heat conduction coefficient, and compressive strengths decreased. This reduction was caused by the fact that the expanded glass had a low density (0.17-0.23 g/cm(3)), a low water absorption rate (23%), and a low heat conduction coefficient (0.0639 W/m K). In the article, the elasticity module of the concrete was investigated using UPV method. The dynamic elasticity module of the concrete samples containing expanded glass was 6-40.23 GPa. The dynamic elasticity module of sand containing concrete samples was higher.
Keywords: Lightweight concrete; Expanded glass; Mechanical properties; Elasticity modulus